2021
DOI: 10.1002/jcsm.12736
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic role of sarcopenia in elderly patients with classical Hodgkin lymphoma: a multicentre experience

Abstract: Background Elderly classical Hodgkin lymphoma (cHL) (ecHL) is a rare disease with dismal prognosis and no standard treatment. Fitness‐based approaches may help design appropriate treatments. Sarcopenia has been associated with an increased risk of treatment‐related toxicities and worse survival in various solid tumours, but its impact in ecHL is unknown. The aim of this retrospective multicentre study was to investigate the prognostic role of sarcopenia in ecHL. Methods We included newly diagnosed >64 years ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Neto et al ( 24 ) did not highlight any effects of sarcopenia on mortality and toxicity in patients with lymphoma undergoing autologous hematopoietic stem cell transplantation ( 24 ). Results of a multicenter study by Zilioli et al ( 25 ) suggested that there was no significant association between sarcopenia and either PFS or OS in patients with Hodgkin's lymphoma ( 25 ). Sarcopenia was also not associated with mortality in patients with hematopoetic malignancies in a subgroup analysis carried out by Au et al ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neto et al ( 24 ) did not highlight any effects of sarcopenia on mortality and toxicity in patients with lymphoma undergoing autologous hematopoietic stem cell transplantation ( 24 ). Results of a multicenter study by Zilioli et al ( 25 ) suggested that there was no significant association between sarcopenia and either PFS or OS in patients with Hodgkin's lymphoma ( 25 ). Sarcopenia was also not associated with mortality in patients with hematopoetic malignancies in a subgroup analysis carried out by Au et al ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have been published so far about the prognostic role of sarcopenia in elderly lymphoma and in most cases were based upon DLBCL [ 6 ]. Specific studies about elderly HL are scarce [ 20 ]. Zilioli et al [ 20 ] found a positive correlation of sarcopenia measured as a static parameter with PFS and OS only in men.…”
Section: Discussionmentioning
confidence: 99%
“…Specific studies about elderly HL are scarce [ 20 ]. Zilioli et al [ 20 ] found a positive correlation of sarcopenia measured as a static parameter with PFS and OS only in men. However, the role of body composition changes during treatment is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…13 Zilioli et al showed that sarcopenia was related to unfavourable outcomes in older patients with classical Hodgkin lymphoma. 14 Another study by Lieffers et al found that sarcopenia was a predictor of postoperative infection and rehabilitation care in older patients with colorectal cancer. 15 Until now, there have been limited data about the relationship between sarcopenia and the prognosis of older patients with ICC.…”
Section: Introductionmentioning
confidence: 99%